The Utilization and Extraction Method of Nanocellulose: A Review - Farrah Fadhillah Hanum; Aster Rahayu; Nafira Alfi Zaini Amrillah; Yoga Nawaki Helmi Mustafa (Universitas Nusa Bangsa, 2023)
Currently, the use of nanocellulose is very broad in various fields, such as pharmaceuticals, cosmetics, and electronics industries. In its development, this nano-sized cellulose is widely used as a reinforcement nanocomposite nanofiller. Nanocellulose has several advantages, including its large surface area, very lightweight, easy to shape, ability to break through the performance limits of conventional materials, and having a high economic value. Nanotechnology develops based on new properties produced by nanomaterials as advanced materials. Therefore, the factor of the extraction process method must be considered to produce nanocellulose that has good quality and large quantity. Nanocellulose extraction can be accomplished in a variety of ways depending on the raw material but is generally done through a combination of chemical, mechanical, and biological treatments.